Gender's Moderating Impact on Financial Capability, Training, and MSME Performance - Pujiastuti, Arum; Sulistiyanto, Tri Joko (EAJ (Economic and Accounting Journal), 2025)
This study investigates the influence of financial capability and entrepreneurship training on MSME performance, with gender as a moderating variable. Using a quantitative approach, data was collected from 116 MSME owners in Kendal Regency via questionnaires distributed both online and in person. Financial capability significantly impacts MSME performance, highlighting the importance of effective financial management and access to resources. However, training does not have a direct significant effect, likely due to short duration and delayed impacts. Gender does not significantly affect MSME performance or moderate the influence of financial capability and training, indicating equal opportunities for male and female entrepreneurs. The findings emphasize the critical role of financial capability over training or gender in improving MSME success.